Nonna's Spiritual Journey Back Home - Culos, Raymond (Italian Canadiana, 2021)
This is a story of a young bride, typical of many Italian women of her generation, who struggled with the proposition of having to leave all she knew and loved behind to join her husband and a new life in ‘America’. Threading this common story of emigration, journeying, and settling, however, are the memories of a devoted grandson who, charmed by grandma’s fascinating narratives of “home”, embarks in his adult life on his own journey, back to the fount of his origins. Nonna Artemisia had left Italy on the promise to her father that she would endeavour to return someday to be with him again. The author, captivated by his grandmother’s lifelong feeling of separation, symbolically returns her spirit to its original familial home.